Forecasting of activity process indexes for Dubrava forestry - Ruzgas, Tomas; Cibulskytė, Rasa (Lietuvos matematikos rinkinys, 2008)
The forecasting models of activity process indexes and statistical software SAS for support the decisionmaking is presented in this paper. The models and software were developed using applied statistics methods, object programming technology.
Keywords: Dubrava forestry; forecasting; time series analysis